Financial restructuring and target capital structure: An iterative algorithm for shareholder value maximization. Issue 2 (14th May 2018) - Mielcarz, Paweł; Osiichuk, Dmytro; Owczarkowski, Ryszard
Abstract : Purpose: This paper aims to present an iterative algorithm that yields the amount of debt contracting/repayment or equity investment necessary to achieve the target capital structure. The model also helps to estimate the gains in shareholder value that result from financial restructuring process and lead to the optimal leverage ratio. Design/methodology/approach: The paper maintains that certain benchmarks – i.e. industry average financial leverage and unlevered beta corrected for cash – make it possible to determine the parameters of the optimal capital structure for the company, so a failure to adjust to the target may result in value destruction. Findings: The paper presents an iterative algorithm that yields the amount of debt contracting/repayment or equity investment necessary to achieve the target capital structure. Originality/value: The proposed algorithm overcomes the methodological problems of existing approaches to the estimation of shareholder value gained through financial restructuring and implicitly solves the circularity problem in the calculation of the weighted average cost of capital.